2022
DOI: 10.3389/fimmu.2022.897223
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Safety and Efficacy of an Oral Probiotic-Based Vaccine Against Aspergillus Infection in Captive-Bred Humboldt Penguins (Spheniscus humboldti)

Abstract: Aspergillosis is a fungal infection caused mainly by Aspergillus fumigatus that often results in respiratory disease in birds. Aspergillosis is a major cause of morbidity and mortality in captive-bred penguin species. Currently, there is no registered vaccine to prevent aspergillosis. Recent research demonstrated that oral administration of gram-negative bacteria expressing high levels of galactose-α-1,3-galactose (α-Gal) modulates anti-α-Gal immunity and protects turkeys from clinical aspergillosis caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Nevertheless, while most studies focused on the direct or indirect detection of microorganisms in wild or captive Humboldt penguins have been addressed to pathogenic issues [ 44–46 ], in one study describing the gut microbiota of captive Humboldt penguins, the presence of Acinetobacter spp. ranked among the taxa with the highest relative abundance [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while most studies focused on the direct or indirect detection of microorganisms in wild or captive Humboldt penguins have been addressed to pathogenic issues [ 44–46 ], in one study describing the gut microbiota of captive Humboldt penguins, the presence of Acinetobacter spp. ranked among the taxa with the highest relative abundance [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, instead of other measures, the risk of acquiring Aspergillus spores from the rearing environment must be eliminated. New technologies, such as diagnosis with image analysis [ 25 , 27 ], plasma biomarkers [ 38 ], and probiotic-based vaccination [ 39 ], might be useful in reducing the incidence of aspergillosis among penguins. However, environmental interventions might be an effective and easy method for decreasing the risk of aspergillosis, which should be considered a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, to our knowledge, there has been only one study investigating the intestinal microbiota of Spheniscus species ( Spheniscus humboldti ). However, this study did not show the composition of the intestinal microbiota at the phylum level, and its sample size was low ( n = 4) [ 22 ]. A previous study showed that the predominant bacteria in captive Chinstrap penguins are Proteobacteria, Firmicutes, Fusobacteria and Bacteroidetes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%